Research priorities and best practices for managing climate risk and climate change adaptation in Australian agriculture. Issue 1 (2nd January 2019) - George, David A.; Clewett, Jeff Frank; Lloyd, David; McKellar, Richard; Tan, Poh-Ling; Howden, Mark; Rickards, Lauren; Ugalde, David; Barlow, Snow
ABSTRACT: The challenges of climate change adaptation in agriculture are examined through the lens of priorities for research, and the use of best management practices (BMPs) to better manage climate risks. The methods and results have two parts. Firstly, a case study from the northern grains region examines the use of BMPs for managing climate risks associated with both climate variability and climate change. A series of industry workshops developed and tested a suite of 24 BMP standards for growing dryland grain crops, including four BMPs on risk management based on the Australian Standards for Risk Management. Secondly, priorities for research on climate change adaptation in the primary industries sector are described and evaluated to assess needs for updating, in response to industry and environmental changes. The analysis reveals strong reasons for increasing the priority given to education and extension on risk management and for developing BMPs for both incremental and transformative adaptation, and especially for deriving methods to achieve widespread adoption of BMPs for managing extreme climatic events. Collaborative development of BMPs involving farmers'/industry/scientists is the process most likely to derive robust BMPs to withstand the complexities of climate risk and build greater resilience of communities and ecosystems.